LA TRANSITION DEMOCRATIQUE MOBUTISTE FACE A L’AVENEMENT D’UNE REBELLION LIBERATRICE KABILISTE AU CONGO-ZAIRE - Tabu , Gabriel Ekili (IJRDO - Journal of Social Science and Humanities Research, 2021)
The fundamental contradictions created by institutional stakes of the Mobutiste political transition lead to the end of the latter by a rebellion carried by ethnico-racial and the nebulous armed groups, for mixing locales unilateralized and stranger . This illegal victorious processus of change under Laurent-Désiré Kabila’s leadership,drawing lukewam legitimacy of ideology of liberation of conglese people from Mobutu’s dictatorship forks dizzily towards another kind (type) of authoritarianism fought paradoxically by the companions and (sponsors) godfathers of the « revolition ».